Differential Item Functioning of Performance-Based Assessment in Mathematics for Senior High Schools - Abraham Gyamfi (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
The purpose of the study was to validate performance-based assessment in mathematics (Quantitative Reasoning) for Senior High Schools for Differential Item Functioning (DIF). The study sought to found out if the five-items on a newly developed performance-based assessment in mathematics (quantitative reasoning items) has DIF. The study employed descriptive research design embedded in Graded Response Model (GRM). Stratified, census, simple random sampling and purposive samplings procedures were employed to select 750 SHS Three students in the Western Region from three categories of SHS. The Performance-based assessment test was used as the main data collection instruments. Data were analyzed with winGEN and independent t test using SPSS. It was also found that with the exception of the linear equation item that showed DIF for category A and C schools, there was no presence of DIF in the items for both gender and category of school. Based on the findings, it was recommended that performance-based assessment should be an integral part in the methods of assessment lessons and courses at both the colleges of education and universities and that major method of assessment strategy in teaching and learning of mathematics.